Cholinesterase and Inflammation: Exploring Its Role and Associations with Inflammatory Markers in Patients with Lower Extremity Artery Disease - Maximilian Mitteregger; Sabine Steiner; Andrea Willfort-Ehringer; Thomas Gremmel; Renate Koppensteiner; Michael Gschwandtner; Eva-Luise Ritter-Hobl; Christoph W. Kopp; Patricia P. Wadowski (Biomedicines)
Background: Inflammation is a major driver of atherosclerotic diseases including lower extremity artery disease (LEAD). Serum cholinesterase (ChE) has been shown to impact cardiovascular health and regulate inflammatory processes. Objectives: The aim of this study was to investigate the relationship between serum ChE levels and inflammatory markers in patients with hemodynamically relevant iliac artery stenosis, assessing its potential role in the inflammatory processes of lower extremity artery disease (LEAD). Methods: In the following retrospective data analysis, we investigated 150 patients with hemodynamically relevant iliac artery stenosis as documented by a delta peak systolic velocity (δPSV) ≥ 1.4 m/s and investigated the possible influence of ChE on established inflammatory markers, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and hemoglobin-to-platelet ratio (HPR), along with other routine laboratory or vascular parameters. Results: ChE levels differed significantly between patients with stable claudication (Fontaine stage II) and critical ischemia (Fontaine stages III and IV): 7.76 mg/dL (6.55–8.7 mg/dL) vs. 6.77 mg/dL (5.85–7.48 mg/dL), p = 0.004. Using the spearman correlation coefficient, testing of NLR and ChE revealed a highly significant inverse correlation, with a coefficient of −0.303 (p < 0.001). Additionally, a weak inverse correlation was observed between PLR and ChE, with a coefficient of −0.162 (p = 0.049). Patients with an elevated body mass index (BMI) showed increased levels of serum ChE, with a spearman correlation coefficient of 0.298 (p < 0.001). Conclusions: The observed correlations in this study depict active inflammation in LEAD with an emphasis on patients with critical ischemia. Serum ChE could serve as a potential biomarker for inflammation in patients with LEAD, particularly in distinguishing between stable claudication and critical ischemia. Future research is needed to explore the role of ChE as a complementary biomarker, offering insights into the cholinergic regulation of inflammation in LEAD.